Surgical counts in open abdominal and pelvic surgeries in a university hospital: a best practice implementation project. Issue 1 (22nd March 2021) - Gomes, Eduardo T.; Galvão, Mayana C.B.; Shimoda, Gilcéria T.; de Oliveira, Larissa B.; de Araújo Püschel, Vilanice A.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Introduction: Counting of accountable items used during surgery, frequently called 'the count', is a fundamental practice to ensure that items such as surgical instruments, sponges and sharps are not forgotten within patients. Although inadvertently leaving behind a sponge or instrument at the end of an operation is a rare event, it is an error that may have serious implications. Objectives: The aim of this evidence implementation project was to contribute to promoting evidence-based practice in surgical counts in open abdominal and pelvic surgeries and thereby improving the outcomes of the surgical patients at a surgical centre of a university hospital. Methods: The current evidence implementation project used the JBI Practical Application of Clinical Evidence System and Getting Research into Practice (GRiP) audit and feedback tool. The JBI Practical Application of Clinical Evidence System and GRiP framework for promoting evidence-based healthcare involves three phases of activity: first, establishing a project team and undertaking a baseline audit based on evidence-informed criteria; second, reflecting on the results of the baseline audit and designing and implementing strategies to address non-compliance found in the baseline audit informed by the JBI GRiP framework; third, conducting a follow-up audit to assess the outcomes of the interventions implemented to improve practice, and identify future practice issues to be addressed in subsequent audits. These three phases were performed over a period of 6 months, from August 2017 to March 2018. Results: The baseline audit revealed deficits between old and best practice in all criteria. Barriers for implementation of a protocol for surgical counts were identified, and strategies were implemented. The postimplementation (follow-up) audit showed improvement in compliance with best practice in six of the audit criteria selected except two, a multidisciplinary team approach to decrease retained surgical items, and limited staff hand-offs during surgical procedures to ensure the same team is present in all counting episodes. Conclusion: The main achievements of the study included substantial increases in compliance with best practice. However, registration and report and commitment of all members of surgical team to apply the entire protocol, avoiding to skip any step, persist as challenges.